The semi-intensive production model: A strategy based on emergy and economic analyses to realize sustainability in the ecosystem of Sistani beef cattle raising in Iran. (15th August 2022) - Amiri, Zahra; Maghsoudi, Ali; Asgharipour, Mohammad Reza; Nejati-Javaremi, Ardeshir; Campbell, Daniel E.
Abstract: Cattle rearing can benefit from the environmental support of native wetlands, through the establishment and proper management of units suitable for raising Sistani cattle ( Bos indicus ) around the Hamoun Wetland in the Sistan region of Iran. In this way, it is possible for cattle rearing to benefits from the environmental support of the wetland, thereby improving food security, fostering economic and social development, and contributing to the environmental protection of this sensitive region. In addition, helping to preserve the Sistani cattle breed, which is in danger of extinction, will be a significant benefit. This study was conducted from 2019 to 2020 on three different beef cattle production systems in the Sistan region. Both emergy and economic analyses were used to examine these production systems; 1) rearing the Sistani breed in an extensive production system, 2) rearing Sistani cattle in a semi-intensive production system, and 3) rearing an exotic breed within an intensive production system. In the extensive indigenous system, the amount of emergy supporting Sistani breed production was 2.30E+17 sej, which was less than the other two systems. Based on the economic output/input ratio (O/IEmV ), the yield of the Sistani breed in the semi-intensive system was 62% higher than that breed in an open system and 84% higher than exotic breeds in the intensive system. The values of the Emergy Exchange Ratio (EER), Transformity (Tr), and Specific Emergy (SpE) indices revealed that the Sistani breed outperformed the open system by 1.5 times and the exotic breed by 2 times in the intensive system. However, the sustainability of the Sistani breed raised under extensive and semi-intensive production systems is not guaranteed in the long run, given their dependence on production from the Hamoun wetland and the long-term meteorological data on declining rainfall, as well as, the decisions of Afghanistan, on the allocation of water rights to the upper watershed and to the downstream wetlands, which poses the risk of reducing the free environmental resources supplied to the Iranian wetland system. Due to these risk factors, designing the system for Sistani cattle raising as a semi-intensive production system is recommended as the way to most reliably attain the aforementioned benefits. Highlights: Emergy evaluation can be successful in selecting the right production model to improve the agroecosystems sustainability. The structure and quantity of purchased inputs differed greatly across the systems studied. Analyzing the economic and environmental condition of agro-ecosystems may assist evaluate their overall sustainability. Emergy analysis is a comprehensive and explanatory method for assessing the sustainability of agro-ecosystems.